2019
DOI: 10.1111/gcb.14756
|View full text |Cite
|
Sign up to set email alerts
|

The functional role of temperate forest understorey vegetation in a changing world

Abstract: Temperate forests cover 16% of the global forest area. Within these forests, the understorey is an important biodiversity reservoir that can influence ecosystem processes and functions in multiple ways. However, we still lack a thorough understanding of the relative importance of the understorey for temperate forest functioning. As a result, understoreys are often ignored during assessments of forest functioning and changes thereof under global change. We here compiled studies that quantify the relative import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
129
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(153 citation statements)
references
References 143 publications
(205 reference statements)
4
129
0
2
Order By: Relevance
“…In addition to altered microclimatic conditions, forest edges, as opposed to forest interiors, are also characterized by a higher seed influx of non-forest species (Devlaeminck, Bossuyt, & Hermy, 2005), differences in disturbance regimes, and higher nitrogen (N) and carbon (C) stocks (Remy et al, 2016). These biotic and abiotic factors all influence understorey plant communities, which contain more than 80% of total plant species' richness in temperate forests and are essential for several ecosystem functions such as nutrient cycling, carbon dynamics and tree regeneration (Gilliam, 2007;Landuyt et al, 2019;Whigham, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to altered microclimatic conditions, forest edges, as opposed to forest interiors, are also characterized by a higher seed influx of non-forest species (Devlaeminck, Bossuyt, & Hermy, 2005), differences in disturbance regimes, and higher nitrogen (N) and carbon (C) stocks (Remy et al, 2016). These biotic and abiotic factors all influence understorey plant communities, which contain more than 80% of total plant species' richness in temperate forests and are essential for several ecosystem functions such as nutrient cycling, carbon dynamics and tree regeneration (Gilliam, 2007;Landuyt et al, 2019;Whigham, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Understorey vegetation comprises a major component of plant diversity [1], which contributes to the structural complexity of forests, heterogeneous habitats for other biotic groups, water holding capacity, and nutrient retention [2]. Although understorey vegetation often contributes relatively a small portion to the biomass of overall forest ecosystems, it plays a critical role in nutrient cycling and energy flow due to the high turnover rates of understorey vegetation [1,[3][4][5][6][7]. Several studies have revealed that the abundance, diversity, and composition of understorey vegetation change temporally with stand development following stand-replacing disturbances [8], and that the forest overstorey strongly mediates understorey vegetation [9].…”
Section: Introductionmentioning
confidence: 99%
“…global change affecting overstorey productivity), understorey research has predominantly focussed on biodiversity responses, motivated by the knowledge that the understorey largely determines the vascular plant diversity in temperate forests (Gilliam, ). Although the marginal contribution of the understorey to the total standing biomass in a forest (see, e.g., Zhang, Chen, & Taylor, ) might justify the greater interest in the overstorey when it comes to ecosystem functioning, more and more evidence is becoming available that the understorey can play an important functional role as well (Landuyt et al, ). The understorey can, for example, alter tree regeneration and growth rates resulting from competition with trees for water, nutrients and light (Bloor et al, ; Giuggiola et al, ; Watt, Whitehead, Richardson, Mason, & Leckie, ).…”
Section: Introductionmentioning
confidence: 99%
“…Price, Dunham, Carleton, & Band, ). The importance of all these effects jointly depends on understorey biomass and its species composition, the latter driving the understorey's functional signature (Gilliam, ; Landuyt et al, ). Understorey biomass, however, is generally considered as the most important indicator for understorey functioning, especially when considering the understorey's role in water and nutrient cycling, food provision for ungulates and its effect on tree regeneration (e.g.…”
Section: Introductionmentioning
confidence: 99%